Pola Belajar Mahasiswa Disabilitas Netra pada Masa Pandemi Covid-19 di UIN Raden Mas Said Surakarta - Handayani, Ilham Putri; Achadi, Muh Wasith; Khairi, Alfin Miftahul (MASALIQ, 2022)
The Covid-19 pandemic has forced the government to establish a distance learning system and online learning in the implementation of education in Indonesia. Online learning is indeed not to difficult if carried out by normal students, but it is different for children with special needs, especially children with visual impairments who have limitations in their vision. The various problems implied by this pandemic have drastically changed the learning patterns of children with visual impairments. The porpuse of this research is to study further about the learning patterns of students with visual impairments at UIN Raden Mas Said Surakarta. This research is included in qualitative research using descriptive method. The data sources used were 2 students with visual impairments in the Islamic Counseling Guidance Study Porgram. The Techniques used in data collection are interviews and documentation. The result of this study revealed that the leraning patterns of students with visual impairments during the Covid-19 pandemic at UIN Raden Mas Said Surakarta included: (1) independent learning patterns, (2) group learning pattern or discussions and, (3) guided learning patterns. Of the three patterns, the learning system that blind students go through is very different form face-to-face learning, starting from preparation for learning, how to do assignments and how to take part in learning that really needs help form various parties even though they have used supporting applications in learning.